PELATIHAN BAHASA INGGRIS PARIWISATA UNTUK CADDY GOLF DI NEW KUTA GOLF, PECATU, KABUPATEN BADUNG, PROVINSI BALI: indonesia - Supartini, Nih Luh; Susanti, Luh Eka; Sulasmini, Made Ayu (Jurnal Pengabdian Masyarakat Sabangka, 2022)
In order to increase the resources of the tourism sector in Bali, improving English as a means of communication is very important to do. The objective of this Community Partnership Program is to provide English language training for golf caddy at New Kuta Golf Peactu. This English course training aims to facilitate the lack of human resources (caddy) in communication skills in using English. All caddy are women at least high school graduates. This training activity was carried out before the Covid-19 outbreak, so that all activities can take place face to face (offline). The result of this activity is to improve the caddy's ability to communicate in English properly and correctly and more meaningfully. In this case, another goal is to minimize the use of body language for the caddy to avoid miscommunication between the caddy and foreign guests. Keywords: Training; Communication; Skills; Caddy